Impact of Solid Surface Energy on Wettability of CO2-brine-Mineral Systems as a Function of Pressure, Temperature and Salinity - Arif, Muhammad; Barifcani, Ahmed; Lebedev, Maxim; Iglauer, Stefan (2017)
CO 2 storage refers to the methods employed to inject CO 2 in depleted oil and gas reservoirs and deep saline aquifers for long term storage of CO 2 with the objective to reduce the anthropogenic CO 2 emissions. Wettability and interfacial tension are two important multiphase parameters which are used to characterize the flow behavior of CO 2 in reservoirs. Numerous studies have reported wettability data of CO 2 -brine systems on various rock forming minerals as function of pressure, temperature and salinity. However, the associated trends have not been physically well-understood and require considerable attention which is objective of our present work. In this work, we apply Neumann's equation of state method to our measured contact angle data for CO 2 -brine-mica systems and contact angle data of CO 2 -brine-quartz from Sarmadivaleh et al., 2015. Our results indicate that for mica, solid-CO 2 interfacial tension decrease with pressure and salinity and increase with temperature. Moreover, solid-liquid interfacial tension decrease with temperature and decrease with salinity. For quartz, although the solid-CO 2 interfacial tension decrease with pressure and increase with temperature, yet solid-liquid interfacial tension increase with temperature which explains the increase in contact angle with temperature for quartz. Overall, we find that results are in accordance with wettability data as function of pressure, temperature and salinity. We thus conclude that hotter reservoirs with lower injection pressure and lower brine salinities exhibit relatively better water wetting state and hence better seal capacity leading to higher CO 2 storage potential. We also conclude that solid surface energy approach adequately explains the dependency of wettability on pressure, temperature and salinity.